(untitled) (Research, Society and Development, 2020)
The objective was to prepare goat’s milk yogurt with the addition of pineapple (Ananas comosus) and noni (Morinda citrifolia) jams and to evaluate the product’s physical-chemical, microbiological and sensory parameters. Five treatments of goat’s milk yogurt were developed with different concentrations of pineapple and noni jellies (0, 0.5, 1.25, 2.5 and 5%). In the treatments, the physical-chemical composition (humidity, ash, lactose, acidity, pH, fat, protein), microbiological (coliforms at 45ºC, mesophiles, psychrotrophic, salmonella spp., And positive coagulase staphylococcus) were determined, and in relation to the analyzes sensory, 20 (twenty) trained tasters performed tests such as: quantitative descriptive analysis (QDA), purchase intention and acceptance test. There was no significant difference (p <0.05) between treatments for the physical-chemical variables, showing that the attributes pH, titratable acidity, fat and protein, as well as the microbiological profile were within the standards in force by legislation. Regarding sensory evaluation, the sample with 5% of pineapple and noni jellies was well accepted by the tasters. It is concluded that the treatment with 5% of the jellies has stood out from the others, being characterized as an innovative product for the commercialization of dairy derivatives of caprine origin.